TASHKENT NEIGHBORHOODS (MAHALLAS) IN THE DESCRIPTION OF SCIENTISTS AND RESEARCHERS - Nargiza Shonazarova; Hayitboy Kholmirzaev; Barno Urazimbetova; Kamola Umarkulova; Tursinali Kholkuziev (The Bioscan, 2024)
the article examines the reflection of the history of Tashkent mahallas in historical sources, literature and official documents and their historical-ethnographic and socio-demographic description. It analyzes the works of scientists and researchers who conducted scientific research on urban mahallas from a historical point of view. The article studies historical materials and literature related to the way of life of the Uzbek people as a neighboring community, that is, the specific content and essence of mahallas, from the point of view of historiography.